PENGARUH KUALITAS LAYANAN DAN TINGKAT KEPUASAN PENGUNJUNG TERHADAP LOYALITAS CUSTOMER PADA OBJEK WISATA DI PANTAI SEJARAH - Adillah, Rafiqah; Nazmah, Nazmah (LPPM STIE Muhammadiah Bandung, 2024)
The tourism industry is an industry that has high development potential and has an important role in economic growth and community welfare. The aim of this research is to determine the influence of service quality and level of visitor satisfaction on customer loyalty at Historic Beach. The research methodology used is quantitative descriptive research. The population used in the research were visitors to Historic Beach located in Perupuk Village, Limapuluh Pesisir District with a sample of 255 people. When selecting samples, use the purposive sampling method. Instrument The survey instrument used was a Likert scale-based questionnaire. Data were analyzed using SPSS Version 22 software and the results were presented in table form. Research results using Multiple Linear Regression hypothesis testing. It was found from the t test that service quality and level of visitor satisfaction had a positive and significant effect on visitor loyalty. Continuing with the F Test, service quality and level of visitor satisfaction simultaneously influence visitor loyalty at Historic Beach. The adjusted R square value is 0.597 or 59.7% with a fairly significant level of correlation. As a result, it can be said that the variables of service quality (X1), level of visitor satisfaction (X2), and customer loyalty (Y) at Historic Beach influence each other by 59.7% and the rest is influenced by other factors. Researchers recommend that further research be carried out using a more diverse and extensive sample size and variables. So that it can better represent visitor loyalty.